Robust flow vector estimation for echocardiography with extended Nyquist velocity using dual-PRF approach: a flow phantom study. (14th March 2023) - Okada, Yuki; Kanno, Naoya; Bhatti, Anam; Ishii, Takuro; Saijo, Yoshifumi
Abstract: To enable quantitative assessments of multi-directional blood flow dynamics such as those in the heart, a two-dimensional (2D) flow vector estimation method using dual-angle Doppler measurements with a sector ultrasound probe was developed. However, that technique was prone to aliasing artifacts because the dual-angle transmissions reduced the pulse repetition frequency (PRF) and Nyquist flow speed by half for each Doppler measurement. To overcome this problem, this study devised a new dual-angle vector flow imaging framework with extended Nyquist velocity using the dual-PRF de-aliasing method. In the proposed framework, the Nyquist flow speed was doubled to 930 mm s −1 compared with the conventional dual-angle approach. Imaging experiments demonstrated that the proposed framework could correct the aliasing artifacts in color Doppler frames and successfully derive 2D flow vectors comparable to particle image velocimetry measurements with a relative error of −14.5% in the fast and 35.2% in the slow flow phases in a pulsatile flow condition.